Comment on "Analysis of Crossover-Induced Capacity Fade in Redox Flow Batteries with Non-Selective Separators" [J. Electrochem. Soc., 165 A3144 (2018)]. Issue 12 (30th July 2019) - Nemani, Venkat Pavan; Smith, Kyle C.
Abstract : The particular overpotential definition used in expressing the kinetic rate constants given by Marcus-Hush-Chidsey (MHC) theory was incorrect in our original article [ J. Electrochem. Soc., 165, A3144 (2018)] and has been corrected here to be expressed in terms of the standard overpotential. Implementation of the corrected rate constants is necessary to reproduce near-equilibrium variations of cell voltage with state-of-charge, a property that is assured by the de Donder relation. However, we find that the RFB performance metrics presented in our original article (discharge capacity utilization, capacity fade, and time-averaged polarization) change insignificantly after correction of this theory and its implementation in our numerical model. While future studies should acknowledge this subtle point, no conclusions from our original article were changed by the error in the theory originally presented.